Perceived benefits and perceived barriers of having safe practices and healthy lifestyles to prevent epidemic diseases among people living in the border areas of Ubon Ratchathani Province - Kulchaya Loyha; Charoenbut, Pattaraporn (UBRU Journal for Public Health Research, 2019)
This study aimed to survey attitudes towards perceived benefits and perceived barriers of having safe practices and healthy lifestyles to prevent epidemic diseases among people living in the border areas of Ubon Ratchathani Province. This study was a cross-sectional descriptive study. It investigated two sample groups: patients who were sick with communicable diseases and people who were at risk of getting infected from communicable diseases. The two sample groups included Thais and foreigners who received hospital services in the border areas of Ubon Ratchathani Province between 2012 - 2013. Equipped with the two sample groups, seven hospitals in Ubon Ratchathani were examined. They were Khammaraj, Phochai, Srimuangmai, Khongjam, Sirinthorn, Boontarik, and Najaroy hospitals. The survey forms were created and distributed to two sample groups in seven hospitals. The collected data were analyzed by using descriptive statistics, that is percentage and frequency distribution. The results found that most of the samples had their attitudes towards perceived benefits and perceived barriers of preventing epidemic diseases at a moderate level (49.2%). In addition, the majority attitudes agreed with wearing a mask at all times to help protect from being infected from the airborne diseases in crowded places. Moreover, the sample groups accepted the idea that following the news about epidemic diseases continuously would help them to be aware of preventing themselves from being infected by communicable diseases (83.5 % and 72.0 %, respectively). Although most subjects perceived the benefits and barriers of practicing themselves to prevent epidemic diseases at a moderate level, some subjects were still found to be at a lower level. Interestingly, the practices of most people for preventing epidemic diseases were in a moderate level. The results were relevant to the social cognitive theory which is the basis of the Health Belief Model. The model states that if a person has good knowledge and perception in some certain cases, the good knowledge and the fine perception will affect his behaviors or actions to do well in those cases.